A Case Report of Neonatal 2019 Coronavirus Disease in China. (12th March 2020) - Wang, Shaoshuai; Guo, Lili; Chen, Ling; Liu, Weiyong; Cao, Yong; Zhang, Jingyi; Feng, Ling
Abstract: In December 2019, the coronavirus disease (COVID-19) caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in China and now has spread in many countries. Pregnant women are a population susceptible to COVID-19 and are more likely to have complications and even progress to severe illness. We report a case of neonatal COVID-19 in China with pharyngeal swabs testing positive by real-time reverse-transcription polymerase chain reaction assay 36 hours after birth. However, whether the case is a vertical transmission from mother to child remains to be confirmed.